IMPLEMENTASI KEBIJAKAN PENINGKATAN MUTU SEKOLAH TINGGI DAN AKADEMI BIDANG KESEHATAN MELALUI SISTEM PENJAMINAN MUTU INTERNAL (SPMI) DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Wiwik Suryandartiwi Anggarawati (DIA: Jurnal Administrasi Publik, 2019)
The aim of this study is to identify and to analyze the implementation of The Internal Quality Assurance System Policy (SPMI), the advantage factors and the obstacles of the systems and to identify the model of implementation which is appropriate for the Health Education Institutions in The Province of DIY. This study used qualitative approach with qualitative descriptive format. This study finds some results. They are; (1) The implementation of The Internal Quality Assurance System Policy (SPMI) in Health Education Institutions in The Province of DIY are vary. However, most institutions have been implementing the system which is in accordance with the regulation, although there are some shortcomings of completeness of the data. (2) Commitment and good communication between institutions are the advantages while the poor in the implementation of good quality culture, high load of work, and the incompleteness of documents of quality are the obstacles. (3) The appropriate system implementation for the Health Education Institutions in The Province of DIY is the one which is integrated with Controlling Integrated Education System (CIES).